Experimental Studies on Memory in Conference Interpretation - Daró, Valeria (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1997)
AbstractSeveral studies in cognitive psychology and neuropsychology have shown that memory is not a unitary function of human cognition, since it comprises several multi-modal systems, which can be mutually independent. This article describes: a) the present state of the art on the functional organization of the most relevant memory systems (working memory and explicit vs. implicit memory systems), and b) what experimental studies have so far revealed about the role ofmnestic systems during the process of simultaneous and consecutive interpretation. Since these studies suggest that memory is multifaceted, there cannot and should not be a single, unique way to teach and acquire the techniques and strategies of these two types of conference interpretation, which sometimes are erroneously considered reciprocally complementary.